The 14th colony [compact disc, unabridged] - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2016)
Shot down over Siberia in what was to be a simple meet-and-greet-mission, ex-Justice Department agent Cotton Malone is forced into a fight for survival against Aleksandr Zorin, whose loyalty to the former Soviet Union has festered for decades into an intense hatred of the United States. Before escaping, Malone learns that Zorin and another ex-KGB officer, this one a sleeper still imbedded in the West, are headed overseas to Washington D.C. In a race against the clock that starts in the frozen extremes of Russia and ultimately ends at the White House itself, Malone must not only battle Zorin, he must also confront his deepest fear, a crippling weakness that he's long denied but one that now jeopardizes everything. Print run 400,000.